Youth and volunteerism: What gives? - Glendinning, Emma (Institutional Knowledge at Singapore Management University, 2017)
As a volunteer, I’m one of many in the world. Data from Figure 1—a survey about volunteering among a number of OECD countries—shows that at least one-fi fth of the population in many countries engages in volunteer activities.1 Though Figure 1 does not provide details on the amount of time spent volunteering—or indeed if this volunteering is one-off or recurring—we see that volunteering rates in Australia, Canada and the United States stand out for being particularly high, whereas those in Italy, Spain and Sweden are remarkably lower than the OECD average.2